Institutional Mission Education as a Form of Teaching. Issue 3 (27th May 2017) - Procario-Foley, Carl B.
Abstract: This article examines how the field of religious education informs religiously based colleges and universities as they teach about their institutional missions. A discussion of the audiences, languages, and the temporal orientations of institutional mission education is intended to provide insights and parameters as mission offices chart their futures and justify their purposes to diverse constituencies. Particular attention is given to current challenges, namely the unjust structures and practices that have shaped institutions and their missions. Utilizing examples from his home institution, the author argues for a "present approach" to mission education.